Corynebacterium heidelbergense sp. nov., isolated from the preen glands of Egyptian geese (Alopochen aegyptiacus) - Braun, Markus S.; Wang, Erjia; Zimmermann, Stefan; Wink, Michael (Systematic and applied microbiology, 2018)
Two strains (pedersoliT and girotti) of a new species of bacteria were isolated from the preen glands of wild Egyptian geese (Alopochen aegyptiacus) from the river Neckar in southern Germany in two subsequent years. The strains were lipophilic, fastidious, Gram-positive rods and belonged to the genus Corynebacterium. Phylogenetically, the isolates were most closely related to Corynebacterium falsenii DSM 44353T which has been found to be associated with birds before. 16S rRNA gene sequence similarity to all known Corynebacterium spp. was significantly <97%. Corresponding values of rpoB showed low levels of similarity <87% and ANIb was <73%. G+C content of the genomic DNA was 65.0mol% for the type strain of the goose isolates, as opposed to 63.2mol% in Corynebacterium falsenii. MALDI-TOF MS analysis of the whole-cell proteins revealed patterns clearly different from the related species, as did biochemical tests, and polar lipid profiles. We therefore conclude that the avian isolates constitute strains of a new species, for which the name Corynebacterium heidelbergense sp. nov. is proposed. The type strain is pedersoliT (=DSM 104638T=LMG 30044T).
Gesehen am 06.08.2019